2017
DOI: 10.1044/2016_ajslp-16-0040
|View full text |Cite
|
Sign up to set email alerts
|

Employer Reactions to Adductor Spasmodic Dysphonia: Exploring the Influence of Symptom Severity and Disclosure of Diagnosis During a Simulated Telephone Interview

Abstract: Symptom severity in ADSD influences employer perceptions during the phone interview process. Incorrect assumptions may be made about applicants with severe symptoms, and apparentness of symptoms influences whether or not disclosure is recommended. Results have implications for counseling individuals with ADSD who are navigating the job interview process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Health related stigma was often found to lead to discriminatory behaviours by employers, which made it challenging for people with disabilities to find or maintain sustainable employment. First, health related stigma negatively affected hiring decisions: a quarter of the selected studies showed that employers were reluctant to hire people with disabilities [17,20,30,33,37,39,42,43,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Once an employer was aware that a job candidate had a disability, the employer was inclined to focus more on the disability rather than on his/her actual abilities and skills [62,63].…”
Section: Employersmentioning
confidence: 99%
“…Health related stigma was often found to lead to discriminatory behaviours by employers, which made it challenging for people with disabilities to find or maintain sustainable employment. First, health related stigma negatively affected hiring decisions: a quarter of the selected studies showed that employers were reluctant to hire people with disabilities [17,20,30,33,37,39,42,43,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Once an employer was aware that a job candidate had a disability, the employer was inclined to focus more on the disability rather than on his/her actual abilities and skills [62,63].…”
Section: Employersmentioning
confidence: 99%
“…Participants in Groups I and II found that positive emotional outlooks helped them persevere. They also had developed different strategies for disclosure and approaching difficult situations, which has been linked to better outcomes in a variety of everyday settings, such as employment (Isetti et al, 2017). In contrast, participants in groups III and IV had a diverse, but not necessarily adaptive repertoire of coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, everyone receiving BoNT injections has to manage the cyclical nature of the treatment including common side-effects, such as breathy voice and transient dysphagia that often follow injections, and the return of original symptoms of LD as the effects of BoNT wear off at the end of each cycle (Novakovic et al, 2011;Paniello et al, 2008). LD usually starts between the ages of 30 and 50 years, thus potentially having a significant impact on employment and related responsibilities that is somewhat unique from other conditions that tend to occur later in life (Isetti et al, 2017;Meyer et al, 2013;Smith et al, 1998;Tanner et al, 2011).…”
Section: Importance Of Capturing the Client's Perspective On Life Participationmentioning
confidence: 99%
“…Laryngeal diseases represent a broad spectrum of conditions that include non‐urgent elective issues, and urgent or emergent conditions where time to intervention appropriately differs between them. Another layer of complexity unique to laryngeal issues relates to the potential negative impacts on employability, absenteeism, and general public perception that occurs among patients with voice or respiratory disorders that may impact need for intervention beyond traditional life and limb considerations to improve quality of life 9–15 . Furthermore, certain laryngeal conditions are treated nonsurgically through voice therapy and respiratory training methods, which involves speech pathologists.…”
Section: Introductionmentioning
confidence: 99%
“…Another layer of complexity unique to laryngeal issues relates to the potential negative impacts on employability, absenteeism, and general public perception that occurs among patients with voice or respiratory disorders that may impact need for intervention beyond traditional life and limb considerations to improve quality of life. 9 , 10 , 11 , 12 , 13 , 14 , 15 Furthermore, certain laryngeal conditions are treated nonsurgically through voice therapy and respiratory training methods, which involves speech pathologists. This adds another parallel wait time system as those treatment options span multiple sessions rather than a single operation that attempts to treat the condition.…”
Section: Introductionmentioning
confidence: 99%